Rancang Bangun Smart Aquarium Menggunakan Metode Fuzzy Logic Mamdani untuk Ikan Botia Berbasis Internet of Things - Faturrahman, Vieri; Nurussa’adah, n/a; Maulana, Eka (Jurnal Mahasiswa TEUB, 2024)
Botia fish are freshwater ornamental fish with high visual appeal and economic value. However, this species is currently threatened due to overfishing and challenges in breeding. Botia fish typically thrive in optimal environments with a pH range between 5.0 - 7.5, temperatures of 24-31°C, and good water quality management, including dissolved water particles. Suitable parameters can enhance the fish’s skin color and maintain their health. Therefore, this research aims to design and implement an Internet of Things (IoT)-based Smart Aquarium system using the Mamdani Fuzzy Logic method to improve the maintenance of Botia fish. The system monitors and controls water quality in real-time, including water temperature, dissolved particles, water pH, and manages automatic feeding. In this study, the methods employed include system flowchart design, equipment specifications, and hardware development using an Arduino Uno microcontroller and ESP8266. Sensors such as the temperature sensor (DS18B20), pH, and TDS were installed to measure aquarium conditions, while actuators like heaters, fans, peltier modules, servos, buzzers, and pumps were used to control the state of the Smart Aquarium. The results of this study showed an average accuracy of sensors, actuators, and the system above 97,136 % and demonstrated the system’s ability to regulate temperature and water quality optimally for Botia fish. This research is expected to provide an innovative solution for the challenges of Botia fish maintenance in the context of a sustainable environment.Keywords: The Botia fish, Smart Aquarium, Internet of Things, Mamdani Fuzzy Logic